Muscle strength and incidence of depression and anxiety: findings from the UK Biobank prospective cohort study. Issue 4 (8th June 2022) - Cabanas‐Sánchez, Verónica; Esteban‐Cornejo, Irene; Parra‐Soto, Solange; Petermann‐Rocha, Fanny; Gray, Stuart R.; Rodríguez‐Artalejo, Fernando; Ho, Frederick K.; Pell, Jill P.; Martínez‐Gómez, David; Celis‐Morales, Carlos
Abstract: Background: Depression and anxiety are the leading mental health problems worldwide; depression is ranked as the leading cause of global disability with anxiety disorders ranked sixth. Preventive strategies based on the identification of modifiable factors merit exploration. The aim of the present study was to investigate the associations of handgrip strength (HGS) with incident depression and anxiety and to explore how these associations differ by socio‐demographic, lifestyle, and health‐related factors. Methods: The analytic sample comprised 162 167 participants (55% women), aged 38–70 years, from the UK Biobank prospective cohort study. HGS was assessed at baseline using dynamometry. Depression and anxiety were extracted from primary care and hospital admission records. Cox proportional models were applied, with a 2 year landmark analysis, to investigate the associations between HGS and incident depression and anxiety. Results: Of the 162 167 participants included, 5462 (3.4%) developed depression and 6614 (4.1%) anxiety, over a median follow‐up period of 10.0 years (inter‐quartile range: 9.3–10.8) for depression and 9.9 (inter‐quartile range: 9.0–10.8) for anxiety. In the fully adjusted model, a 5 kg lower HGS was associated with a 7% (HR: 1.07 [95% CI: 1.05, 1.10]; P < 0.001) and 8% (HR: 1.08 [95% CI: 1.06, 1.10]; P < 0.001) higher risk of depression and anxiety, respectively. Compared with participants in the sex and age‐specific highest tertiles of HGS, those in the medium and lowest tertiles had an 11% (HR: 1.11 [95% CI: 1.04, 1.19]; P = 0.002) and 24% (HR: 1.24 [95% CI: 1.16, 1.33]; P < 0.001) higher risk of depression and 13% (HR: 1.13 [95% CI: 1.06, 1.20]; P < 0.001) and 27% (HR: 1.27 [95% CI: 1.19, 1.35]; P < 0.001) higher risk of anxiety, respectively. The association of HGS with depression was stronger among participants with average or brisk walking pace (vs. slow walking pace; P interaction < 0.001). The association with anxiety was stronger in those participants aged ≥58 years (vs. ≤58 years; P interaction = 0.002) and those living in more affluent areas (vs. deprived; P interaction = 0.001). Conclusions: Handgrip strength was inversely associated with incident depression and anxiety. Because HGS is a simple, non‐invasive, and inexpensive measure, it could be easily used in clinical practice to stratify patients and identify those at elevated risk of mental health problems. However, future research should assess if resistance training aimed at increasing HGS can prevent the occurrence of mental health conditions.